Uji Kinerja Turbin Angin Sumbu Horizontal Bilah Inverse Taper Berdiameter 2,6 M Di Gedung C Fakultas Teknik Universitas Riau - Husaini, Fachri; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Electrical energy requirements which continues increase and diminishing fossil fuels resulting research in the field of renewable wind energy developing rapidly, one of the renewable energies is wind turbines. This study aims to determine the performance of the horizontal axis wind turbine by using the type of blade inverse taper NACA 4412 with a composite fiber empty palm fruit bunch combined with fiberglass. The wind turbine is placed on top of the building C Faculty of Engineering, Riau University at height ±15 m. The output power is measured using a 300 Watt generator. The data take form of wind speed, air temperature, voltage and shaft rotation speed. Data collection was carried out using arduino uno which was recorded in the data logger for 1 day, namely on 15 and 16 August 2020. After testing the wind turbine, the highest wind speed data was obtained, namely on August 16 with a wind speed of 5.12 m/s at 12:28:13 WIB. The maximum shaft rotation obtained from the maximum wind speed is 9.4 Rpm with a Cp of 0.08 and a TSR of 0.1. Keyword : wind turbine, wind speed, inverse taper.